2021
DOI: 10.3390/cancers13081940
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives on the TNM Staging for Lung Cancer

Abstract: Since its conception by Pierre Denoix in the mid-20th century, the tumor, node, and metastasis (TNM) classification has undergone seven revisions. The North American database managed by Clifton Mountain was used to inform the 2nd to the 6th editions, and an international database collected by the International Association for the Study of Lung Cancer, promoted by Peter Goldstraw, was used to inform the 7th and the 8th editions. In these two latest editions, it was evident that the impact of tumor size was much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…There are novelties concerning the classic "anatomical" parameters of TNM. An example of this is a more accurate description of the invasion of the chest wall with the involvement of its different layers (parietal pleura, bony structures and soft tissue) which could potentially show a different prognosis [47]. Indeed, Sakakura et al found that an operated patient with T3 tumors with invasion of the parietal pleura alone had better survival that a patient with deeper involvement of the chest wall (5-year survival rates 50% and 36.7%, respectively, p = 0.028).…”
Section: Future Perspectives With the Ninth Tnm Stagingmentioning
confidence: 99%
“…There are novelties concerning the classic "anatomical" parameters of TNM. An example of this is a more accurate description of the invasion of the chest wall with the involvement of its different layers (parietal pleura, bony structures and soft tissue) which could potentially show a different prognosis [47]. Indeed, Sakakura et al found that an operated patient with T3 tumors with invasion of the parietal pleura alone had better survival that a patient with deeper involvement of the chest wall (5-year survival rates 50% and 36.7%, respectively, p = 0.028).…”
Section: Future Perspectives With the Ninth Tnm Stagingmentioning
confidence: 99%
“…Because our patient data were selected from 2004 to 2015, we first used version 6th TNM staging to compare with our prognostic model via DCA, and then, we completed the transformation of TNM staging and evaluated the patient data according to the 8th edition. There is no essential difference in staging between the two editions, while the staging of the eighth edition TNM is more detailed [ 31 ]. This model is superior to TNM staging, whether it is the 6th ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the 7th edition of the TNM staging system, the IASLC committee suggested that the overall disease burden of LNs might have the most important in uence on survival outcomes rather than the anatomical location of LN involvement (7). Some published studies indicated that the burden of metastatic LN stations might re ect a distinct N-subcategory with more aggressive behaviour than the traditional Nclassi cation, and an increase in the number of involved LNs is a poor prognostic factor (4,6,(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%